The Labor Market Experience of Engineers in North America - Boyd, Archibald; Gross, Andrew; McKay, Raymond (Relations industrielles / Industrial Relations, 1971)
The authors have undertaken a major project which they envision ultimately as an on-going analysis of the labor market behavior of technical and scientific manpower in highly developed economies. Their paper represents a first step in this direction.